KOMUNIKASI ANTARPRIBADI GURU DENGAN SISWA TUNAGRAHITA RINGAN DALAM MENGEMBANGKAN KEMANDIRIAN SISWA DI SEKOLAH LUAR BIASA (SLB) NEGERI PEMBINA PEKANBARU - Andi Arivai; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Children with mentally disabled have the same right to take education as normal child in general. One of the educational institutions for children with special needs in the city of Pekanbaru is SLB N Pembina Pekanbaru. Interpersonal communication is needed in the learning process between teachers and mentally disabled students. Through this interpersonal communication makes students feel closer to their teachers. This study was conducted to determine how the openness, empathy, being supportive, positive behavior and equality are conducted by teachers with mentally disabled students in developing the independence of mild mentally disabled students in a state of special school (SLB N) Pembina Pekanbaru.This study used qualitative research methods with symbolic interaction approach and descriptive. Informants in this study were teachers, mentally disabled students and parents of mild mentally disabled students with purposive method. The techniques of data collection is done by observation, interview and documentation. To achieve the validity of the data in this study, researcher used the extension of participation and triangulation.The result of this study showed that interpersonal communication between teachers and mild mentally disabled students has gone well. The opennes attitude by teachers such as say hello to student, asking what they feel and think. The emphaty teachers did involved verbal greetings or non verbal act. Being supportive including motivate students and praised for what student have done. Positive behaviour including be friendly and smile to student. Equality attitude in a way acting as a not smart people and not too patronizing student. Interpersonal communication that teachers did give the positive impacts for the development of student’s independence.Keyword : interpersonal comunication, teachers, mild mentally disable, independence